Effects of organic solvents on immobilized lipase in pectin microspheres - Costas, L. (2008)
Lipase from Brevibacillus agri 52 was found stable up to 90% diethylenglycol (DEG), glycerol (GLY), and 1,2 propanediol (1,2 PRO) at 37 °C for 1 h and the stability was reduced only approximately 20% after 12 h incubation, but in 40% dimethylsulfoxide (DMSO), lipase activity was stable only for 1 h. Inhibition of the biocatalysts with dimethylformamide (DMF) was detected at 20% solvent concentration. In water immiscible systems, the stability of lipase in n-hexane, n-tetradecane and n-heptane resembles the water activity, but in the presence of isobutanol, 1-hexanol, and butylbutirate, the stability was significantly reduced. Lipase 52 precipitates in the presence of 50% acetone or ethanol/ water mixtures, but enzymatic activity was partially recovered by adding 20% GLY, DEG, 1,2 PRO, or DMSO to the reaction mixture. Furthermore, by increasing DEG in 70% DMF/ DEG mixtures, the lipase activity was protected. Encapsulation of lipase in pectin gels cross-linked with calcium ions brings three to four times more enzymatic activity in 70% water miscible organic solvents compared to aqueous systems.